Saberes tradicionais indígenas da comunidade Nova Esperança para a aprendizagem em ciências da natureza no ensino fundamental - Oliveira, Lúcia Helena Soares de (2021)
The present work stems from the disquiet in the teaching practice about the Teaching of Nature Sciences in Indigenous School Education in Elementary School in the Municipality of Manaus/AM. The Brazilian Constitution of 1988 deals with the school right of native peoples as a differentiated education, based on the use of indigenous languages, valuing the ancient knowledge and knowledge of these peoples, aiming at training indigenous people to act as teachers in their communities. Given the understanding that knowledge of culture is necessary to organize an educational practice that supports these assumptions, since, on the national scene, resistance movements are visible, opposing the catechizing School Education resulting from the historical processes that permeate school spaces indigenous peoples. Even with the resistance movement, the scarcity of pedagogical proposals elaborated by the indigenous people is still visible, as they recognize that they are at a disadvantage due to the precarious education that has been offered by the formal system. Based on this understanding, we aim to analyze how the traditional culture of the Nova Esperança Indigenous Community can contribute to the process of teaching and learning scientific knowledge in Nature Sciences in Indigenous School Education. The constituents of this study are based on the assumptions of the qualitative approach, the focus of participatory research and the ethnographic methodology for the knowledge of the traditional culture of Comunidade Nova Esperança. We verified that the cultural traits pointed out in this work are knowledge that permeate the daily lives of indigenous peoples, neither as an attractive element nor as a party ornament, but traditional culture is based on values and knowledge for the survival of human beings. We noticed a movement to rescue traditional culture by the indigenous people themselves and this movement mainly involves the educational space, with propositions of contextualization of knowledge that for us is knowledge, for indigenous people it is science. The knowledge mentioned are traits present in the language, on the walls of houses, in everyday objects, in clothing, in crafts and in the narratives that make up the collective collection of this people. The possibility of mediating traditional culture for teaching in School Education in different fields of knowledge is notorious. And this effectiveness results from the development of a methodology using active methods in the context of Intercultural Education. The teaching experience mediated by the indigenous teachers themselves points to the mediation potential of traditional knowledge in line with the objects of knowledge in Natural Sciences for the teaching and learning process in Elementary School.